Tradisi Apitan sebagai Budaya Keagamaan Warga Nahdlatul Ulama di Desa Gebangan Kecamatan Tegowanu Kabupaten Grobogan - Anti Kurnia Fitri (Journal of Nahdlatul Ulama Studies, 2022)
Apitan is an annual communal rite widely recognized as sedekah bumi, a thanksgiving ceremony for agricultural abundance and a collective supplication for safety. This study examines (1) the ritual sequence of Apitan in Gebangan Village, Tegowanu District, Grobogan Regency; (2) the symbolic meanings embedded in ritual objects and performances; and (3) the social–religious and character-education values reproduced through Apitan as a lived religious culture among Nahdlatul Ulama (NU) villagers. Employing a qualitative design, data were collected through participant observation, in-depth interviews, and documentation. The findings show that Apitan is institutionalized through village deliberation (rembug desa) and enacted through opening remarks, greetings, collective prayers (including shalawat, prayers for ancestors, and al-Fatihah), communal dining (bancakan/kenduri), gamelan (klenengan), and an all-night wayang kulit performance with agrarian narratives such as Sri Mulih. Symbolic interaction operates as villagers attribute shared meanings to gunungan, tumpeng, and agrarian tools, consolidating a collective understanding of gratitude, blessing, and social harmony. The tradition strengthens social values responsibility, cooperation, and concord while articulating character-education values such as religiosity, honesty, discipline, patriotism, tolerance, peacefulness, environmental care, social care, and accountability. Supporting factors include strong communal legitimacy and village governance, while the principal constraint is the cost of organizing large-scale events.